Optimasi Penugasan Menggunakan Metode Hungarian Maksimasi untuk Meningkatkan Efektivitas Alokasi Sumber Daya (Seimbang dan Tidak Seimbang) - Anabella Monica Agustine Simanjuntak (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The Hungarian method is a mathematical optimization algorithm used to solve assignment problems by finding the optimal allocation of resources to tasks. This research examines the application of the Hungarian method for both balanced and unbalanced maximization assignment problems. The balanced assignment problem involves an equal number of workers and jobs, while the unbalanced problem deals with unequal numbers. The study aims to analyze the effectiveness of the Hungarian method in solving maximization problems through mathematical modeling and algorithmic implementation. The research methodology includes literature review, mathematical analysis, and computational testing using various case scenarios. Results demonstrate that the Hungarian method can effectively solve both balanced and unbalanced maximization assignment problems by converting them into minimization problems through matrix transformation. The balanced cases show direct application of the classical Hungarian algorithm, while unbalanced cases require the addition of dummy variables to achieve matrix balance. The method proves to be efficient with polynomial time complexity O(n³), making it suitable for real-world applications. The research concludes that the Hungarian method provides optimal solutions for resource allocation problems in various organizational contexts, contributing to improved operational efficiency and cost-effectiveness in decision-making processes.